067 Bannwarth syndrome presentation of neuroborreliosis, with radiological evidence of CNS demyelination. Issue 12 (14th November 2019) - Soane, Tim; Shaikh, Fahad; Mair, Grant; Baggott, Amy; Pal, Suvankar
Abstract : A 59 year old right handed IT professional presented with left shoulder pain, which evolved to whole arm weakness, numbness and pain, before affecting his right arm and then legs to a lesser degree. Over subsequent weeks he developed right facial weakness and circumferential numbness around his torso. Examination revealed a mixed picture of lower motor neurone signs and long tract signs. CSF analysis showed a pleocytosis of 415 white cells, predominantly lymphocytes and elevated protein at 3.49 g/dL. MRI head showed a number of periventricular and brainstem lesions with appearances and locations typical for demyelination. Nerve conduction studies were compatible with a demyelinating polyradiculoneuropathy. Lyme serology showed elevated IgG positive and borderline elevated IgM. His CSF antibody levels were compatible with neuroborreliosis. He was treated with ceftriaxone 4 g daily for 21 days. The Bannwarth syndrome is a triad of painful polyradiculopathy and facial nerve palsy and lymphocytic pleocytosis, and is a presentation of neuroborreliosis typically associated with European neuroborreliosis caused by infection with Borrelia afzelii and garinii genospecies.